DETERMINANTS OF FIRM VALUE ON CONSUMPTION SECTOR IN INDONESIA - Ji Kyoung Jang; Prio Utomo (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- The purpose of study is to understand the dominan determinants factor which is debt to asset ratio, current ratio, dividend payout ratio and firm size that will influence the firm value in consumer goods companies in Indonesia. To able to maintain dan increase the Indonesia economic growth, Investment and consumption are two main contributor to sustainable economic growth in Indonesia. The study seek for more understanding the determinant that influence the firm value that could support investor decision in consumer goods The study seek for relationship between determinants to predict firm value in the consumption industry which previously done in other sector with inconclusive result. The sample used in this research came from the financial report of 10 of 50 public listed company in IDX between 2013-2017 has high credibility and stability with purposive sampling. The Multiple Regression of modeling are used to analyze the relationship between determinants. The debt to asset ratio, current ratio, and firm size are affect the firm size significantly except for the devident payout ratio, with debt to asset ratio with the most effecting factor. DAR can reflect how financially stable a company is. The higher the ratio, the higher the degree of leverage and, consequently, the higher the risk of investing in that company. Keywords: Firm Size; Consumer Goods; Debt to Asset Ratio; Current Ratio; Firm Size; Dividend Payout Ratio